Epigenetic Drug Interventions in Breast Cancer: A Narrative Review of Current Research and Future Directions - Sarah Bibi Mungly; Evelyn Priya Peter; Ling-Wei Hii; Chun-Wai Mai; Felicia Fei-Lei Chung (Progress in Microbes and Molecular Biology)
Breast cancer is a life-threatening disease known for its extensive molecular heterogeneity. The study of the breast cancer epigenome has revealed potential avenues for improving breast cancer treatment risk stratification, early detection, and treatment. With renewed interest in epigenetic-modifying pharmaceutical agents, namely DNA methyltransferase inhibitors (DNMTi), histone deacetylase inhibitors (HDACi), bromodomain and extra-terminal inhibitors (BETi), and enhancer of zeste homolog 2 inhibitors (EZH2i), there have been extensive preclinical and clinical studies to evaluate the safety and efficacy of these agents as potential treatments for breast cancer. In this review, we summarise and present the preclinical and clinical evidence for epigenetic drugs in treating breast cancer. We review the challenges associated with the translation of these findings into improved patient outcomes, namely the optimisation of dosage and treatment regimens, and the emergence of resistance. These challenges have been widely recognised in the field and are of utmost importance for the successful implementation of personalised medicine. While there is strong evidence that epigenetic alterations, consisting of changes in DNA methylation, histone modifications, and non-coding RNAs, play a crucial role in breast cancer initiation and development, additional research is warranted to elucidate the safety profile of long-term interventions involving epigenetic drugs and to validate the role of epigenetic markers in disease diagnosis, prognosis, and personalised treatment.